Inactivation of dermatophyte infection by nonthermal plasma on animal model - Scholtz, Vladimír; Soušková, Hana; Švarcová, Michaela; Kríha, Vítezslav; Živná, Helena; Julák, Jaroslav (Medical mycology, 2017)
Superficial fungal infections are a major epidemiological issue with increasing prevalence and are a common global problem. This article describes experimental therapy of superficial fungal skin infection using low-temperature plasma. Groups of guinea pigs were artificially infected with Trichophyton mentagrophytes SK 3286 dermatophyte and treated with plasma produced by a DC cometary discharge with an inserted grid. The course of infection was a week shorter and milder in animals treated by plasma than that in nontreated animals, the significant lowering of dermatophytic germs also occurred in the treated group. The exposure to plasma causes no harm to experimental animals. The results allow for the development of a new dermatophytoses therapy by low temperature plasma treatment.
Keywords: antifungální látky; plazmové plyny; Administration, Topical; Female; výsledek terapie; Dermatomycoses; zvířata; Guinea Pigs; dermatomykózy; guinea pig; ženské pohlaví; Male; dermatophytosis; Antifungal Agents; Treatment Outcome; skin mycosis; cometary discharge; morčata; Plasma Gases; Animals; aplikace lokální; mužské pohlaví; Disease Models, Animal; Trichophyton; modely nemocí na zvířatech